Integrated risk management of hazardous processing facilities. Issue 1 (9th August 2018) - Song, Guozheng; Khan, Faisal; Yang, Ming
Abstract : Processing facilities handling large amounts of hazardous substances are attractive targets for terrorists. Thus, these work sites are exposed not only to accidents but also to intentional threats. Some research has separately studied risk caused by either potential accidental events or terrorist acts. However, studies focusing on integrated risk assessment and management (dealing with both safety and security issues) are lacking. This paper proposes an approach to assess and manage integrated risks. This method is based on an influence diagram which incorporates safety and security‐related factors into one framework. It considers the effects of management actions on both accidental and intentional risks. This method can help to detect hidden risk (i.e., the risk not recognized during design and operation stages) and ensure to reduce the real risk to an acceptable level by guiding the selection of management actions. The effectiveness of the proposed method is demonstrated using the overfilling risk management of an oil tank. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 42–51, 2019